The night of the Bozos - Slepian, Jan. (New York : E.P. Dutton, 1983)
Thirteen-year-old George and his Uncle Hibbie were a team, a pair of loners separated from other people, but the arrival of an extraordinary carnival girl changes many things for both of them.
7.2
Young Adult
Young Adult
Keywords: Emotional problems -- Fiction; Carnivals -- Fiction; Interpersonal relations -- Fiction; Emotions -- Fiction; Festivals -- Fiction; Human relations -- Fiction